PELAKSANAAN PENEGAKAN HUKUM TINDAK PIDANA NARKOTIKA DI WILAYAH HUKUM KEPOLISIAN RESOR ROKAN HULU - Hotma Marajohan P; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Narcotic crime is against the law, every year has peninggkatan, both in the village and in urban areas because of the crime of transnational narcotics with a high modus operandi, sophisticated technology and is supported by an extensive network, here is expected narcotics police and national institutions to maximize its performance to combat in order to restore public awareness of the dangers of narcotics, in Rokan Hulu narcotics eradication has not done well because dealers are caught not entirely, most of which is caught is a user of narcotics. Based on the above description of this thesis aims are: first, the implementation of the crime of drug law enforcement in the area of Police Law Rokan Hulu. second, barriers in the implementation of law enforcement in the area narcotic crime Police Law Rokan Hulu. Third, efforts are being made to overcome the obstacles in the implementation of the law penegaka narcotic crime in the area of Police Law Rokan Hulu. This type of research the writer uses sociological research methods, because the author directly conduct research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in Police Rokan Hulu, Rokan Hulu District Attorney and Court of Rokan Hulu. Source of data used primary data, secondary data, the data tertiary data collection techniques in this study conducted by interviews, questionnaires, and literature. The results of the deliberations of the study it can be concluded: First, law enforcement narcotic crime in Regional Police Rokan Hulu done with preventive and repressive efforts. Preventive efforts. patrols, conduct legal counseling, while the repressive efforts: do observation, arrest, detention, pengeledahan, foreclosure, inspection. Second, barriers experienced Police Rokan Hulu is a lack of quality and quantity of narcotics investigator personnel, lack of community participation, and the lack of facilities and infrastructure. Third, the efforts made to overcome these obstacles is to cooperate with the relevant agencies in providing counseling dangers of narcotics, to convince the public to be able to be a witness to provide legal protection and utilization of existing infrastructure. Suggestions writer, to make the eradication of narcotics in the jurisdiction of Police Rokan Hulu, the police should be one step ahead of the perpetrators, modus operandi study conducted actors and coordinate with relevant agencies and the police are expected to approach the maximum in outreach role is to actively combat narcotic crime.